2017
DOI: 10.1016/j.jcrc.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of early death from sepsis

Abstract: Purpose Patients with severe sepsis who experience rapid, early deterioration and death are of particular concern. Our objective was to identify predictors of early death in Emergency Department (ED) patients with severe sepsis. Methods Secondary analysis of two prospective studies of adult ED patients with severe sepsis. The primary outcome was early death, defined as death within 24 hours of triage. Results Out of 410 severe sepsis admissions, 20 patients experienced early death. These patients demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 24 publications
2
30
1
1
Order By: Relevance
“…1 It is important to note that, irrespective of ARDS diagnosis, we excluded patients from our study who died during the first 24h after hospital admission because their severe symptoms may have skewed the results. 24 This study had several limitations. Firstly, this was a single centre study with a small sample size which may have led to unintentional selection bias and poor statistical power.…”
Section: Discussionmentioning
confidence: 93%
“…1 It is important to note that, irrespective of ARDS diagnosis, we excluded patients from our study who died during the first 24h after hospital admission because their severe symptoms may have skewed the results. 24 This study had several limitations. Firstly, this was a single centre study with a small sample size which may have led to unintentional selection bias and poor statistical power.…”
Section: Discussionmentioning
confidence: 93%
“…During lung infection, glycolysis results in the production of pyruvate, which is converted by lactate dehydrogenase to lactate under anaerobic conditions [ 32 ]. Serum lactate levels have been use for many years in the assessment of tissue hypoxia and perfusion status, and are often used clinically as an indicator of the severity of sepsis and of patient outcomes in sepsis/septic shock [ 33 35 ]. A previous study showed that a lactate level in arterial blood gas of > 1.8 mmol/L at admission could predict a need for mechanical ventilation, vasopressors, ICU admission or hospital mortality in patients with CAP [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies investigated medium-(3 months) or long-term mortality. Javed et al identified initial serum lactate and modified SOFA score as independent predictors of early (within 24 h) death occurring in almost 5% of patients with severe sepsis in the emergency department [16]. Daviaud et al investigated in a comparable cohort of 543 septic shock patients and found that 32% of all ICU deaths occurred in an early stage, namely within three days after ICU admission [8].…”
Section: Discussionmentioning
confidence: 99%